How dietary patterns affect left ventricular structure, function and remodelling: evidence from the Kardiovize Brno 2030 study - Maugeri, Andrea; Hruskova, Jana; Jakubík, Juraj; Hlinomaz, Ota; Medina-Inojosa, Jose R; Barchitta, Martina; Agodi, Antonella; Vinciguerra, Manlio (Scientific reports, 2019)
Little is still known about the effect of dietary patterns on left ventricular hypertrophy (LVH). Here, we derived dietary patterns by principal component analysis (PCA) and evaluated their association with LV structure, function, and remodelling. Our cross-sectional study included 438 members (aged 25-65 years; 59.1% women) of the Kardiovize Brno 2030 with no history of cardiovascular disease. Two dietary patterns were derived using PCA, namely prudent and western. Primary outcomes were echocardiographic parameters and LV geometric patterns, such as concentric LV remodelling (cLVR), concentric LVH (cLVH), and eccentric LVH (eLVH). Interestingly, participants with high adherence to the prudent dietary pattern had decreased odds of cLVH after adjustment for socio-demographic, clinical and behavioral covariates (OR = 0.24, 95% CI = 0.08-0.88; p = 0.031). By contrast, several echocardiographic parameters increased with increasing adherence to the western dietary pattern, which resulted in higher odds of cLVH among participants with high adherence (OR = 5.38, 95% CI = 1.17-23.58; p = 0.035). Although our findings may have an immediate relevance for public-health strategies, further large-size prospective studies should be encouraged to better understand the observed association and their causality.
Keywords: stravovací zvyklosti; logistické modely; Humans; lidé středního věku; Ventricular Remodeling; Logistic Models; Electrocardiography; Female; Aged; dospělí; senioři; lidé; kardiomegalie; Adult; Cardiomegaly; ženské pohlaví; Male; Middle Aged; Heart Ventricles; mužské pohlaví; Feeding Behavior; remodelace komor; srdeční komory; elektrokardiografie